VD_FINDINFO Jug / 2015 / 50 vom 28. August 2014 - VD Tribunal cantonal (2014)
CONSTATATION DES FAITS, MEURTRE, MEURTRE PASSIONNEL, ASSASSINAT | 111 CP, 112 CP, 113 CP, 47 CP, 398 al. 3 let. b CPP (CH)